The Effect Of Emotional Quotient, Motivation And The Working Environment On Teacher’s Performance With Work Communications As A Moderation Variables In SMK PGRI 1 Giri Banyuwangi - M. Hasyim; Muhammad Firdaus; Yuniorita Indah Handayani (LPPM Institut Teknologi dan Sains Mandala, 2020)
This study aims to determine the effect of emotional intelligence, motivation and work environment on teacher performance with work communication as moderation at SMK PGRI 1 Giri Banyuwangi. The data analyzed came from 35 teacher respondents in SMK PGRI 1 Giri Banyuwangi. Data analysis tools with multiple linear regression and multiple linear regression moderation variables with the interaction test method (MRA). The results of linear regression indicate that partially Emotional Intelligence has no significant effect on Teacher Performance, Motivation has a significant effect on Teacher Performance and the Work Environment has a significant effect on Teacher Performance. Line 2 linear regression with the addition of the independent variable Work Communication shows that partially Emotional Intelligence has no significant effect on Teacher Performance, Motivation has a significant effect on Teacher Performance, Work Environment has a significant effect on Teacher Performance and Work Communication has no significant effect on Teacher Performance. The results of the moderation regression show that work communication partially moderates the effect of Emotional Intelligence on Teacher Performance, Work Communication moderates the effect of motivation on Teacher Performance and Work Communication moderates weakens the influence of the Work Environment on Teacher Performance. Keywords: Emotional Intelligence, Motivation, Work environment, Work Communication and Teacher Performance.